Algorithm for the recognition of fragments of the sky - Опанасенко, В. М.; Каспаревич, А. А.; Шевчук, К. І. (Problems of Informatization and Control, 2013)
The algorithm for recognizing pieces of the sky creeping window (single and widescreen) for determination of the space shown in the picture